2012
DOI: 10.1016/j.stem.2012.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Satellite Cell Activation and Self-Renewal by Par-Complex-Dependent Asymmetric Activation of p38α/β MAPK

Abstract: SUMMARY In response to muscle injury, satellite cells activate the p38α/β MAPK pathway to exit quiescence, then proliferate, repair skeletal muscle, and self-renew, replenishing the quiescent satellite cell pool. Although satellite cells are capable of asymmetric division, the mechanisms regulating satellite cell self-renewal are not understood. We found that satellite cells, once activated, enter the cell cycle and a subset undergoes asymmetric division, renewing the satellite cell pool. Asymmetric localizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
262
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(277 citation statements)
references
References 40 publications
10
262
2
3
Order By: Relevance
“…We next sought to determine whether TRAF6 is required for the expression of PAX7 in satellite cells. Our Western blot analysis confirmed that treatment in promoting progression through the myogenic lineage (32,33). Remarkably, we found that phosphorylated and total protein levels of c-JUN, a direct phosphorylation target of ERK1/2 and JNK, were also significantly diminished as a result of deletion of Traf6 ( Figure 6, E and F).…”
Section: Traf6 Is Expressed In Satellite Cells Of Adult Micesupporting
confidence: 79%
“…We next sought to determine whether TRAF6 is required for the expression of PAX7 in satellite cells. Our Western blot analysis confirmed that treatment in promoting progression through the myogenic lineage (32,33). Remarkably, we found that phosphorylated and total protein levels of c-JUN, a direct phosphorylation target of ERK1/2 and JNK, were also significantly diminished as a result of deletion of Traf6 ( Figure 6, E and F).…”
Section: Traf6 Is Expressed In Satellite Cells Of Adult Micesupporting
confidence: 79%
“…The WNT and TGFβ signaling pathways could induce the fibrogenesis of satellite cells in dystrophic mice (Biressi, Miyabara, Gopinath, Carlig & Rando, 2014). The TNF, AKT, and MAPK signaling pathways participate in the proliferation and differentiation of satellite cells (Motohashi et al., 2013; Troy et al., 2012). However, the synergistic effects of different signaling pathways remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Current understanding has relied on a limited number of sources, with Drosophila being the prime model used to study division properties of neuroblasts, germline stem cells, and intestinal stem cells [1]. In mammalian systems, most advances have been made through the study of mouse radial glial progenitors [4], neocortical progenitors [5], and muscle satellite cells [6]. The more recent recognition of a stem cell population in cancer has led to investigations of asymmetric cell division in this disease, using mammalian systems and Drosophila as models.…”
Section: Introductionmentioning
confidence: 99%